Chromosome-Level Genome Assembly for Acer pseudosieboldianum and Highlights to Mechanisms for Leaf Color and Shape Change - Li, Xiang; Cai, Kewei; Han, Zhiming; Zhang, Shikai; Sun, Anran; Xie, Ying; Han, Rui; Guo, Ruixue; Tigabu, Mulualem; Sederoff, Ronald; Pei, Xiaona; Zhao, Chunli; et al. (Frontiers in Plant Science, 2022)
Acer pseudosieboldianum (Pax) Komarov is an ornamental plant with prominent potential and is naturally distributed in Northeast China. Here, we obtained a chromosome-scale genome assembly of A. pseudosieboldianum combining HiFi and HiC data, and the final assembled genome size was 690.24 Mb and consisted of 287 contigs, with a contig N50 value of 5.7 Mb and a BUSCO complete gene percentage of 98.4%. Genome evolution analysis showed that an ancient duplication occurred in A. pseudosieboldianum. Phylogenetic analyses revealed that Aceraceae family it could be incorporated into Sapindaceae, consistent with the present Angiosperm Phylogeny Group system. We further construct a gene-to-metabolite correlation network and identified key genes and metabolites that might be involved in anthocyanin biosynthesis pathways during leaf color change. Additionally, we identified crucial TCP transcription factors that might be involved in leaf morphology regulation of A. pseudosieboldianum, A. yangbiense and A. truncatum. Overall, this reference genome is a valuable resource for evolutionary history studies of A. pseudosieboldianum and lays a fundamental foundation for its molecular breeding.